1981
DOI: 10.1192/bjp.139.6.494
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and Mental Handicap: A Review

Abstract: Traditionally the sexuality of mentally handicapped people was feared by those who made the rules governing Western societies. Where sexual needs were admitted at all, rigid rules were laid down in order to prevent thementally handicapped members of a society from procreating. Thus arose the segregated and isolated colonies for defectives, prohibitions on marriages (Berg and Nyland, unpublished; Grunewald and Limier, 1979) and laws permitting sterilization of the mentally incompetent which became widespread, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 15 publications
0
19
0
2
Order By: Relevance
“…This could lead to a self‐fulfilling prophecy where they internalise this belief and subsequently restrict their expressions of their sexuality. Importantly, this could perpetuate the historical beliefs whereby people with learning disabilities are regarded as asexual eternal children (Craft & Craft ). Such belief systems have denied people with learning disabilities the opportunities to express aspects of sexuality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could lead to a self‐fulfilling prophecy where they internalise this belief and subsequently restrict their expressions of their sexuality. Importantly, this could perpetuate the historical beliefs whereby people with learning disabilities are regarded as asexual eternal children (Craft & Craft ). Such belief systems have denied people with learning disabilities the opportunities to express aspects of sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) conceptualise sexuality as a multidimensional construct including sex, gender and intimacy that can be expressed via attitudes, behaviours, roles and relationships throughout the lifespan (WHO, ). During the 20th century, negative discourses, attitudes and practices (Craft & Craft, ; Mitchell, Doctor, & Butler, ) towards the sexuality of people with learning disabilities dominated societal belief systems and resulted in people with learning disabilities being denied the opportunity to express their sexuality. Recent research has indicated that support staff now hold more positive attitudes towards the sexuality of adults with learning disabilities (Bazzo, Nota, Soresi, Ferrari, & Minnes, ; Cuskelly & Bryde, ).…”
Section: Introductionmentioning
confidence: 99%
“…Feldman et aL, 1986;Gillberg & Geijer-Karlsson, 1983;Kaminer et at., 1981). For those who are married, the quality of their marriage varies enormously; some are satisfying and harmonious; others are stressful, dysharmonious and unsatisfying (Graft & Graft, 1981;Floor ^i a/., 1975;KoUereia/., 1988;Mattinson, 1975). There is some evidenee that the average IQof affected males who marry is higher than that of married women subjeets.…”
Section: Family Factorsmentioning
confidence: 99%
“…The eurrent consensus amongst researehers is that while rates of retardation jwill overall be higher amongst subjects' ehildren, their average IQwill show a regression to the mean. The risk will be markedly higher if both parents are affeeted (Abramson et aL, 1988;Graft & Graft, 1981;Melton & Scott, 1984;Tymehuk et at., 1987). Sometimes this wUl be due to the transmission of speeific inheritable medical conditions; in other eases non-speeifie genetie faetors may be important.…”
Section: Child Outcomementioning
confidence: 99%
“…The majority of children with mental retardation develop normal secondary sexual characteristics (Craft and Craft, 1981 ). Adolescents with mental retardation require sex education including advice regarding contraception, sexually transmitted diseases and the risk of exploitation.…”
Section: Managementmentioning
confidence: 99%